PEMBUATAN MEDIA AJAR INSTALASI DAN PERAWATAN AC SPLIT - Fatra Aditia; Muhammad Zikri yazi; Sateria, Angga; Ariyanto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Learning media plays a crucial role as a tool in creating an effective teaching and learning process. This final project aims to develop an instructional medium for split AC systems, including the creation of maintenance and installation procedures as teaching and training materials. This educational medium incorporates practical elements, offering both theoretical knowledge and hands-on experience in understanding split AC systems. The teaching method will involve a combination of practice and theory, covering maintenance methods, installation techniques, and disassembly procedures for split AC systems, supported by a syllabus, maintenance modules, installation modules, and disassembly modules. It is expected that this learning media will enable students to master split AC maintenance and installation methods. The implementation of this split AC instructional media has resulted in a 51% improvement in student comprehension, indicating a significant increase in their knowledge. With the enhanced knowledge and skills, students will have better career advancement opportunities in the HVAC industry.